Neocytolysis: How to Get Rid of the Extra Erythrocytes Formed by Stress Erythropoiesis Upon Descent From High Altitude - Mairbäurl, Heimo (Frontiers in Physiology, 2018)
Neocytolysis is the selective destruction of those erythrocytes that had been formed during stress-erythropoiesis in hypoxia in order to increase the oxygen transport capacity of blood. Neocytolysis likely aims at decreasing this excess amount of erythrocytes and hemoglobin (Hb) when it is not required anymore and to decrease blood viscosity. Neocytolysis seems to occur upon descent from high altitude. Similar processes seem to occur in microgravity, and are also discussed to mediate the replacement of erythrocytes containing fetal hemoglobin (HbF) with those having adult hemoglobin (HbA) after birth. This review will focus on hypoxia at high altitude. Hemoglobin concentration and total hemoglobin in blood increase by 20% to 50% depending on the altitude (i.e. the degree of hypoxia) and the duration of the sojourn. Upon return to normoxia hemoglobin concentration, hematocrit, and reticulocyte counts decrease faster than expected from inhibition of stress-erythropoiesis and normal erythrocyte destruction rates. In parallel, an increase in haptoglobin, bilirubin, and ferritin is observed, which serve as indirect markers of hemolysis and hemoglobin-breakdown. At the same time markers of progressing erythrocyte senescence appear even on reticulocytes. Unexpectedly, reticulocytes from hypoxic mice show decreased levels of the hypoxia-inducible factor HIF-1α and decreased activity of the BCL2/adenovirus E1B 19 kDa protein-interacting protein 3 (BNIP3), which results in elevated mitochondrial activity in these cells. Furthermore, hypoxia increases the expression of miR-21, which inhibits the expression of catalase and thus decreases one of the most important mechanisms protecting against oxygen free radicals in erythrocytes. This unleashes a series of events which likely explain neocytolysis, because upon re-oxygenation systemic and mitochondrial oxygen radical formation increases and causes the selective destruction of those erythrocytes having impaired anti-oxidant capacity.